Papel da topografia sobre as linhas de instabilidade no leste da Amazônia - OLIVEIRA, Flávio Augusto Farias D (2019)
This study evaluated the role of topography on the development of squall lines occurring on the coast of the state of Pará through observational studies and numerical modeling. Using satellite rainfall estimate of CMORPH (http://www.cpc.ncep.noaa.gov), with spatial resolution of 0.25°, a quantification of accumulated precipitation associated with the days that occurred squall lines with propagation type 2 during the years 2003 to 2010 was made. Through numerical simulation with the regional model BRAMS (http:// http://brams.cptec.inpe.br) a case study of a squall line that occurred on May 30, 2011, the role of topography was evaluated during its development since its formation, at 15 hours local until 18 hours after its formation. It was observed that precipitation associated with this type of squall line is intensified as it propagates inland. The maximum precipitation is in a region with topography up to 300 meters, where the precipitation rate of this squall line is more intense.